Thermal comfort and performance in the buildings of the new research centre of Petrobras in Rio de Janeiro - Marcondes, Mônica Pereira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2010)
This paper presents the a study of the thermal performance of the new Petrobras research centre, CENPES II, in Rio Janeiro, including free running and air-conditioned buildings. The architectural design was the subject of a national competition in 2004, encompassing over 100.000m2 and ten buildings. According to the design brief, four buildings should be naturally ventilated, whilst six had to be either air-conditioned, due to specific occupation requirements. In the case of naturally ventilated buildings, adaptive comfort was applied as performance criterion, and the environmental assessments were supported by advanced simulation tools. In most of the spaces within the free-running buildings the performance assessments showed environments with similar conditions to the exterior. Considering the working spaces pre-determined to be air-conditioned, the potential for natural ventilation in the working spaces reached 30% of occupation hours, justifying the case for the mixed-mode strategy.